THE INFLUENCE OF CONTEXTUAL TEACHING AND LEARNING APPROACH AND STUDENTS’ GENDER ON MATHEMATICS UNDERSTANDING AT GRADE IV SDN ALANG LAWAS, PADANG - Remiswal; Dorisno (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
The purpose of this study was to describe differences in the understanding of students who learned through CTL approach and students who learned through the conventional approach, to observe the differences in the Mathematics understanding of male students and female students, and to see the interaction between the learning approach and gender on the mathematics understanding. The type of this research was a Quasi Experimental Design with a factorial design (2x2 factorial design). The population in this study was all fourth grade students at SDN Alang Lawas Padang. The samples were students at SDN 37 Alang Lawas as the control class and students at SDN 20 Alang lawas as the experimental class. The results of the research concluded that (1) there were differences in the mathematical understanding of students who were taught by CTL approach and the students who were taught by a conventional approach; (2) there were differences in the mathematical understanding of male students and female students at grade IV SDN Alang Lawas; and (3) there was no significant interaction between learning approaches and gender in influencing students' mathematical understanding.